2019
DOI: 10.1002/jmcd.12123
|View full text |Cite
|
Sign up to set email alerts
|

Understanding HIV Prevention With College‐Going Black Women: An NIMH‐Funded Pilot Study

Abstract: Black women are disproportionately affected by HIV. Limited research has examined race and gender as psychological variables of influence. In this National Institute of Mental Health pilot study, the authors used semistructured interviews to explore the heterogeneity of identity within race and gender and possible interactions with sexual risk perceptions and behavior in a sample of Black women attending college in an urban city. The article presents emergent themes, recommendations, and questions for future r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…variables of RSBs and HIV influences [16]. In a study on comparison of HIV Knowledge, Attitudes, and Sources of STI Information between female and male college students in Taiwan, Tung et al [17] found that while male and female students reported moderate knowledge and attitudes, females had more positive attitudes toward people with HIV/AIDS than males.…”
Section: Demographic Profile Of the Participantsmentioning
confidence: 99%
“…variables of RSBs and HIV influences [16]. In a study on comparison of HIV Knowledge, Attitudes, and Sources of STI Information between female and male college students in Taiwan, Tung et al [17] found that while male and female students reported moderate knowledge and attitudes, females had more positive attitudes toward people with HIV/AIDS than males.…”
Section: Demographic Profile Of the Participantsmentioning
confidence: 99%